How does climate change adaptation strategy accelerate sustainable food security? - Lestari, Etty Puji; Prajanti, Sucihatiningsih Dian Wisika; Soesilowati, Etty; Rahayu, Heffi Christya; Malau, Albert Gamot (Journal of Food Technology Research, 2025)
This study examines the key factors influencing farmers’ decisions to adopt climate change adaptation strategies in agriculture, focusing on Kopeng Village in Semarang, Indonesia. Using a multinomial logit (MNL) model, the article analyzes various strategies in response to climate challenges. It shows that household characteristics, tenure characteristics, and institutional support are important for adaptation decisions. Variables such as age, education level, family size, farming experience, age at first marriage, and age at first childbirth are also significant; older and more educated individuals with larger families are more likely to adopt innovations such as organic fertilizers and fast-growing seeds. Landholding and land size also influence adoption behavior, and the distance from home to agricultural land may hinder the use of organic fertilizers due to transportation logistics. Notably, institutional support—including credit availability, extension services, and farmers’ associations—is critical for the successful adoption of strategies. The government’s role in promoting agriculture, particularly organic farming, is highly anticipated. Through farmer groups, the government can provide necessary technological assistance and digital marketing training to help farmers reach broader markets.